PERTANGGUNGJAWABAN HUKUM PENJUAL ATAS PERJANJIAN JUAL BELI RUMAH YANG SERTIFIKATNYA DIJAMINKAN DI BANK TANPA PEMBERITAHUAN KEPADA PEMBELI - Insyirah, Fioletta Izzah; Hasanah, Uswatun; Umar, Muhamad Abdul; Sullaiman, Mochamad; Murofikoh, Dede Ika (COURT REVIEW, 2025)
There is a problem of the seller's legal responsibility in the house sale and purchase agreement when the title certificate is pledged to the bank without informing the buyer. This research is based on the Civil Code (KUHPerdata) and Law Number 4 of 1996 concerning the Rights of Dependents. Secretly mandating certificates is considered a violation of the principle of good faith, as stipulated in Article 1338 paragraph (3) of the Civil Code, and contrary to Article 10 paragraph (1) of the Law on the Rights of Dependents which forces transparency and registration of the rights of dependents. This study uses a normative juridical method with a legislative approach, decision analysis, and academic literature review. The results of the study stated that sellers can be subject to civil liability based on the principle of default or unlawful acts because the object of sale and purchase is no longer free from the burden of dependents. The Supreme Court's Decision Number 751 PK/Pdt/2019 shows that buyers who have fulfilled their obligations under the Sale and Purchase Agreement (PPJB) continue to suffer losses due to certificates that are pledged without a permit, so that the process of the Deed of Sale and Purchase (AJB) is hampered and has the potential to be auctioned. Analysis from various studies, such as the work of Martha & Fadillah (2020), Nursanti & Fadjriani (2021), and Jennis (2022), confirms that non-disclosure related to dependent rights violates the principles of transparency and protection for buyers. This study concludes that increased legal supervision and education in property transactions is needed to prevent the misuse of certificates and ensure good legal protection for buyers.